Mineral Content Comparison of Sea Grapes (Caulerpa lentillifera) Cultivated in Controlled and Free Waters - Putu Dhena Viyanti Widianita; Kadek Lila Antara; Gressty Sari Br Sitepu; Hamdanul Fain (Advances in Tropical Biodiversity and Environmental Sciences, 2023)
The availability of sea grapes is still very limited, so activities are needed to support the preservation of sea grapes that are rich in mineral content. This research aims to determine growth, water quality, and comparison of mineral content found in C. lentillifera. This type of research is descriptive qualitative. As a research model, namely the mineral content of C. lentillifera in cultivation sites and free waters. On the growth of C. lentillifera, calculate the number of ramuli and water quality, such as pH, temperature, and salinity, with a water quality checker. Data on the mineral content in C. lentillifera was obtained by atomic absorption spectrophotometry (AAS). Based on the results of absorption measurements from several solutions at the cultivation location, the results for Potassium (K) were 2,592.364 mg/kg, Calcium (Ca) with a yield of 896.033 mg/kg, Iron (Fe) with a total of 174.323 mg/kg and for Zinc ( Zn) of 468.804 mg/kg. In the waters of Serangan, based on the results of absorption measurements from several standard solutions, Potassium (K) obtained results of 2,169,732 mg/kg, Calcium (Ca) with results of 1,677,829 mg/kg, Iron (Fe) with results of 1,669.607 mg /kg and for zinc (Zn) with a yield of 44,090 mg/kg.